Realistic biomechanical simulation and control of human swimming - Si, W.; Lee, S. H.; Sifakis, E.; Terzopoulos, D. (ACM Transactions on Graphics (TOG) archive, 2014)
We address the challenging problem of controlling a complex biomechanical model of the human body to synthesize realistic swimming animation. Our human model includes all of the relevant articular bones and muscles, including 103 bones (163 articular degrees of freedom) plus a total of 823 muscle actuators embedded in a finite element model of the musculotendinous soft tissues of the body that produces realistic deformations. To coordinate the numerous muscle actuators in order to produce natural swimming movements, we develop a biomimetically motivated motor control system based on Central Pattern Generators (CPGs), which learns to produce activation signals that drive the numerous muscle actuators.